A scanning electronic microscopy study of the action of different desensitizing agents on bovine dentin - Mollica, Fernanda Brandao [UNESP]; Travassos, Alessandro Caldas [UNESP]; Gomes Torres, Carlos Rocha; Fava de Moraes, Marcelo; Balsamo, Marcelo (My University, 2008)
This study sought to use scanning electronic microscopy (SEM) to evaluate the dentinal tubule occlusion potential of different desensitizing agents. Ten slices of bovine dentin were divided into six fragments, cleaned (using ultrasound), and etched for 15 seconds with a 35% phosphoric acid solution. All but one of the groups received a different desensitizing agent; the sixth group served as a control and received no additional treatment. After the agents were applied, the dentin specimens were analyzed by SEM and scores were assigned based on the extent of tubular obliteration. Only three agents demonstrated tubular sealing that was significantly different from that of the control group.
Keywords: 2 hydroxyethyl methacrylate; acrylic acid resin; calcium chloride; glutaraldehyde; methacrylic acid derivative; nitrate; oxalic acid; phosphate; potassium derivative; potassium dihydrogen phosphate; potassium nitrate; strontium; strontium chloride; animal; cattle; dentin; dentin sensitivity; drug effect; in vitro study; scanning electron microscopy; ultrastructure; Acrylic Resins; Animals; Calcium Chloride; Cattle; Dentin; Dentin Sensitivity; Glutaral; Methacrylates; Microscopy, Electron, Scanning; Nitrates; Oxalic Acid; Phosphates; Potassium Compounds; Strontium